2010
DOI: 10.1523/jneurosci.1546-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Facilitation throughout Human Visual Cortex Lingers in Retinotopic Coordinates after Eye Movements

Abstract: With each eye movement, the image of the world received by the visual system changes dramatically. To maintain stable spatiotopic (world-centered) visual representations, the retinotopic (eye-centered) coordinates of visual stimuli are continually remapped, even before the eye movement is completed. Recent psychophysical work has suggested that updating of attended locations occurs as well, although on a slower timescale, such that sustained attention lingers in retinotopic coordinates for several hundred mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 68 publications
9
77
7
Order By: Relevance
“…A retinotopic code for attended stimuli has also been observed in humans. Indeed, although visual perception is normally facilitated at the location indicated by an attention cue, just after an eye movement, attention can be transiently allocated away from the cue, at its previous retinotopic coordinates (Talsma, White, Mathôt, Munoz, & Theeuwes, 2013;Golomb, Nguyen-Phuc, Mazer, McCarthy, & Chun, 2010;Mathôt & Theeuwes, 2010;Golomb, Chun, & Mazer, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retinotopic code for attended stimuli has also been observed in humans. Indeed, although visual perception is normally facilitated at the location indicated by an attention cue, just after an eye movement, attention can be transiently allocated away from the cue, at its previous retinotopic coordinates (Talsma, White, Mathôt, Munoz, & Theeuwes, 2013;Golomb, Nguyen-Phuc, Mazer, McCarthy, & Chun, 2010;Mathôt & Theeuwes, 2010;Golomb, Chun, & Mazer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some behavioral studies (Talsma et al, 2013;Golomb et al, 2008Golomb et al, , 2010Mathôt & Theeuwes, 2010) show delays in updating the retinotopic coordinates where attention is deployed after a saccade. These delays are compatible with the delay in the ascending fibers (Xu, Wang, Peck, & Goldberg, 2011;Wang, Zhang, Cohen, & 1 Goldberg, 2007) and therefore leave open the possibility that oculoproprioception may contribute.…”
Section: Introductionmentioning
confidence: 99%
“…Because recent reports have suggested that attention updates to spatiotopic coordinates only when behaviorally relevant, and that a "retinotopic attentional trace" lingers at the previously relevant retinotopic location for a brief period after the saccade (23,33), in the present task, we provided ample motivation and time to complete the updating process. Even in these optimal circumstances, spatiotopic behavior was inferior, as if something were "lost in translation."…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpreted this finding as direct evidence for the existence of a transient retinotopic attentional trace. Golomb, Nguyen-Phuc, Mazer, McCarthy, and Chun (2010) followed up on this result by investigating the neural correlate of the retinotopic attentional trace using ERPs and fMRI. In their study, participants attended a fixed location in the center of a display, whereas distracting stimuli were presented briefly at various locations.…”
Section: Introductionmentioning
confidence: 99%
“…ERPs to distractor stimuli presented at the retinotopic and spatiotopic locations were compared with a single control location. Importantly, Golomb, Nguyen-Phuc, et al (2010) presented probe stimuli at two different intervals after the saccade, which allowed them to track the time course of the attentional remapping process. One major finding was that the P1, an ERP component that is known to be sensitive to spatial selective attention (Hillyard, Vogel, & Luck, 1998), representing the suppression of the spatial selection at irrelevant item locations (Talsma, Mulckhuyse, Slagter, & Theeuwes, 2007;Talsma, Slagter, Nieuwenhuis, Hage, & Kok, 2005;Luck et al, 1994), was increased in amplitude for the long postsaccadic delay for both probe locations, compared with a control location.…”
Section: Introductionmentioning
confidence: 99%